Voice of the future? Examining consumer responses to AI-generated voice in brand communication - Ruuska, Matti (2025)
Marketing communication has rapidly changed due to the impact of artificial intelligence (AI). However, there remains limited qualitative research on consumer interpretations and responses to various applications, such as AI-generated voice. This thesis qualitatively examines Finnish consumers’ reactions to AI-synthesized voices and their influence on consumer behaviour. The empirical data was collected through 18 semi-structured interviews conducted with Finnish consumers aged between 19 and 72 during February and March 2025. These interviews explored consumer attitudes towards AI-generated voices, their impact on cognitive processes, and resulting outcomes. The aim was to explore how consumers perceive and interpret AI-generated voices in comparison to human voices within advertising contexts. The findings indicate that consumer responses to AI-generated voices are dualistic: recognizable AI-generated voices trigger a shift from rapid processing to analytical, slow processing, often evoking negative emotions among consumers. In contrast, unrecognised AI-generated voices are processed similarly to natural human voices, maintaining a neutral perception towards the advertisement. Additionally, the perceived “cheapness” associated with AI-generated voices can negatively influence brand credibility, though this effect appears momentary rather than enduring. Contextual factors, such as industry type, consumer attitude towards technology, and disclosure of AI usage, significantly affect consumer perceptions. This thesis provides theoretical contributions by offering new insights into the relatively narrowly researched area of AI-generated voices in marketing. The primary finding is the duality in consumer responses, both in recognizing synthesized voices and reacting to them. For marketing managers, the most meaningful implication is a framework enabling assessment of when AI-generated voice supports marketing efforts and when it may be harmful.